Ultra-high optical nonreciprocity with a coupled triple-resonator structure - Zhen Cao; Yi Fei Xie; Bing He; Qing Lin (New Journal of Physics, 2021)
Optical transmission nonreciprocity as a widely investigated phenomenon is essential to various applications. Many sophisticated mechanisms have been proposed and tested for achieving the optical nonreciprocity on integrated scale, but the technical barriers still exist to their practical implementation. To have an ultra-high transmission nonreciprocity, we consider a simple physical mechanism of optical gain saturation applied to a structure of three mutually coupled cavities or fiber rings. The gain saturation processes in two of its components creates a significantly enhanced optical nonreciprocity that satisfies the requirements for the realistic applications. The structure enjoys two advantages of its wide working bandwidth and the flexibility in choosing its components. Moreover, it is possible to apply the structure to a faithful and non-reciprocal transmission of broadband pulse signals. The structure may considerably relax the constraints on the integrated photonic circuits based on the current technology.